2016
DOI: 10.3389/fpsyg.2016.00380
|View full text |Cite
|
Sign up to set email alerts
|

Using tDCS to Explore the Role of the Right Temporo-Parietal Junction in Theory of Mind and Cognitive Empathy

Abstract: The right temporo-parietal junction (rTPJ) is thought to be closely related to theory of mind (ToM) and cognitive empathy. In the present study, we investigated whether these socio-cognitive abilities could be modulated with non-invasive transcranial direct current stimulation (tDCS) of the rTPJ. Participants received anodal (excitatory), cathodal (inhibitory), or sham stimulation before performing a social cognitive task which included inferring other’s intention (the ToM condition) and inferring other’s emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 38 publications
4
64
0
1
Order By: Relevance
“…The rTPJ is often associated with ToM or the abilitiy to understand other's experiences (Krall et al, 2015;Van Overwalle & Baetens, 2009). To date, anodal stimulation to the rTPJ has failed to affect ToM functioning in healthy adults (Martin, Huang, et al, 2017;Santiesteban, Banissy, Catmur, & Bird, 2015), although one study found reduced ToM accuracy after cathodal stimulation of the rTPJ (Mai et al, 2016). As perspective taking, especially the ability to mentally rotate into an allocentric viewpoint, is considered a prerequisite for ToM (Pearson, Ropar, & Hamilton, 2013), the results of the current study, suggest the rTPJ is causally associated with lower-order processes relevant for ToM, but not the higher-order ToM ability itself.…”
Section: Discussionmentioning
confidence: 99%
“…The rTPJ is often associated with ToM or the abilitiy to understand other's experiences (Krall et al, 2015;Van Overwalle & Baetens, 2009). To date, anodal stimulation to the rTPJ has failed to affect ToM functioning in healthy adults (Martin, Huang, et al, 2017;Santiesteban, Banissy, Catmur, & Bird, 2015), although one study found reduced ToM accuracy after cathodal stimulation of the rTPJ (Mai et al, 2016). As perspective taking, especially the ability to mentally rotate into an allocentric viewpoint, is considered a prerequisite for ToM (Pearson, Ropar, & Hamilton, 2013), the results of the current study, suggest the rTPJ is causally associated with lower-order processes relevant for ToM, but not the higher-order ToM ability itself.…”
Section: Discussionmentioning
confidence: 99%
“…Though the impacts of varying protocols are complex (Horvath et al ., ), anodal tDCS generally promotes depolarisation of resting membrane potentials in underlying cortical tissue (increasing rates of neuronal firing), while cathodal tDCS is understood to increase hyperpolarisation and reduce firing rates (Nitsche et al ., ). tDCS studies suggest TPJ modulation can influence performance in tasks involving mentalising (or related constructs such as moral reasoning, cognitive empathy, visual perspective taking, imitation inhibition, humour appreciation, lie detection, vicarious experience and integrating top‐down and bottom‐up attention) (Santiesteban et al ., ; Sellaro et al ., ; Slaby et al ., ; Sowden et al ., ; Wu et al ., ; Ye et al ., ; Leloup et al ., ; Mai et al ., ; Vandenbroucke et al ., ). This study also improves on prior methodologies using high‐definition transcranial direct current stimulation (HD‐tDCS) rather than standard tDCS.…”
Section: Introductionmentioning
confidence: 99%
“…The rTPJ is often associated with ToM or the abilitiy to understand other's experiences (Krall et al, 2015;Van Overwalle & Baetens, 2009). To date, anodal stimulation to the rTPJ has failed to affect ToM in healthy adults (Martin, Huang, et al, 2017;Santiesteban, Banissy, Catmur, & Bird, 2015) although one study found reduced ToM accuracy after cathodal stimulation of the rTPJ (Mai et al, 2016). As perspective taking, especially the ability to mentally rotate into an allocentric viewpoint, is considered a prerequisite for ToM (Pearson, Ropar, & Hamilton, 2013), the results of the current study, suggest the rTPJ may primarily be involved in lower--order processes relevant for ToM, but not the higher--order ToM ability itself.…”
Section: Discussionmentioning
confidence: 99%